COVID-19 Pandemic's Effect on Performance and Acceleration of Performance Recovery: A Study on Manufacturing Industry in Bangladesh - Golam Shahria (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: The primary aim of this study is to examine the effect of the COVID-19 pandemic during and after this pandemic on manufacturing sectors in Bangladesh. In the context mentioned above, some issues are then taken as the specific objectives.Design/Methodology/Approach: The study was conducted on the manufacturing sectors listed under Dhaka Stock Exchange (DSE). The study's target population was 42 manufacturing companies out of 153 listed on Dhaka Stock Exchange (DSE). Four research variables were used to evaluate sample companies' financial performance and financial position. Documentary analysis, descriptive analysis, data normality test, and Wilcoxon Signed–Rank Test were employed to evaluate the hypotheses. The years of annual reports, 2018-2019 to 2020-2021, were utilized for the documentary analysis of sample companies' financial performance and financial position.Research findings: The study's conclusions demonstrated that this pandemic significantly impacted Bangladeshi companies' financial performance (essentially ROA and ROE) at a 5% significance level compared to before the pandemic. In addition, the recovery growth rate of financial performance of sample companies increased optimistically, and the growth of liquidity position of manufacturing companies was also seen in an advantageous position after the COVID-19 pandemic compared to during the COVID-19 pandemic based on Wilcoxon statistical test tool.Theoretical contribution/Originality: The findings of this study can be used as a source of relevant data by investors or future investors for their investment decisions shortly. The findings of this study will also assist the government in determining or preparing the appropriate tax incentive scheme for the impacted industries and whether the correct sector would profit from the tax incentive scheme.Practitioner/Policy implication: Considering that the COVID-19 pandemic has significantly impacted the import process of raw materials for production from China in specific and from other countries generally, the study advised the government of Bangladesh to boost its logistic and financial support for the local facility of raw materials.Research limitation/Implication: More extensive research is projected to be conducted on the recovery growth rate of financial performance in Bangladesh's sub-sector manufacturing industries.